Dynamic Thiol/Disulphide Homeostasis in Patients With Fibromyalgia - Fatma FİDAN,; Berat Meryem ALKAN,; Fatma Gülçin UĞURLU,; Sinem BOZKURT,; Nebahat SEZER,; Cemile BİÇER,; Özcan EREL,; Özge ARDIÇOĞLU,; Selami AKKUŞ, (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate dynamic thiol/disulphide homeostasis in patients with fibromyalgia syndrome (FMS). Patients and methods: Fifty female patients with FMS (mean age 40.5±7.2 years; range 21 to 55 years) and 40 healthy female controls (mean age 39±9.4 years, range 22 to 55 years) were included in the study. Pain visual analog scale, tender points, Fibromyalgia Impact Questionnaire, and Beck Depression Inventory were evaluated. Age, body mass index (BMI), and symptom durations were also recorded. Native thiol, disulphide and total thiol levels were measured with a novel automated method. Results: Serum disulphide levels were 14.7±3.4 μmol/L and 22.2±3.6 μmol/L in the FMS and control groups, respectively (p<0.001). Native thiol levels were 452.1±33.8 μmol/L and 433.5±37.6 μmol/L in the FMS and control groups, (p=0.015), while total thiol levels were 481.7±35.6 μmol/L and 477.5±38.9 μmol/L in the FMS and control groups, respectively (p=0.593). In the FMS group, disulphide/native thiol percent ratios and disulphide/ total thiol percent ratios were statistically significantly lower and native/total thiol percent ratios were statistically significantly higher than those of the control group. There were no correlations between serum thiol/disulphide profiles and pain scores & clinical variables in patients with FMS. Conclusion: Because of the decreased disulphide and increased native thiol levels, the thiol/disulphide balance has shifted to the reductive side. This metabolic disturbance may have a role in the pathogenesis of FMS.